Application of the Theory of Collective Local Security in Analyzing of the Relation Matters and Patterns in South of Asia - Morteza Nourmohammadi; Mohammad Aref Fasihi Dowlatshahi (رهیافتهای سیاسی و بین المللی)
This paper seeks to apply the theory of collective local security in analyzing of security matters, and issues in south of Asia. The goal of the study is showing the level of natural traits of this theory in clarifying of security issues, hostility and alliance patterns, the types of relation among political units, and knowing the issues of this area. So the main question is that how much benefits has this theory in analyzing the security matters, and issues in south of Asia, and how the knowing of security issues in this area could be achieved? The hypothesis of this research is that because of multidimensional nature of this theory, necessity of studying of twin check of social understanding of situations has a high advantage in analyzing of security matters and issues in south of Asia.  Methodology of the research is descriptive- analytical, and the data was gathered in library. Findings show this critical matter that because of multidimensional nature of this theory, necessity of studying of twin check of social understanding of situations, and knowing the relations of power, has made knowing the types of relations among present political units in south of Asia possible. Essential factors in the findings, on the one hand, are close identical, and cultural relation, on the other hand, is basic material, and the geopolitical dependence in this area provides both the logics and exactness of this theory. Although this theory is not the end of theorizing for this area, it would be an effective theory because of social traits, types of political actions, and local tensions.